A Suppressor/Avirulence Gene Combination in Hyaloperonospora arabidopsidis Determines Race Specificity in Arabidopsis thaliana - Woods-Tör, Alison; Studholme, David J.; Cevik, Volkan; Telli, Osman; Holub, Eric B.; Tör, Mahmut (Frontiers in Plant Science, 2018)
The pathosystem of Arabidopsis thaliana and diploid biotrophic oomycete Hyaloperonospora arabidopsidis (Hpa) has been a model for investigating the molecular basis of Flor’s gene-for-gene hypothesis. The isolates Hpa-Noks1 and Hpa-Cala2 are virulent on Arabidopsis accession RMX-A02 whilst an F1 generated from a cross between these two isolates was avirulent. The F2 progeny segregated 3,1 (avirulent, virulent), indicating a single major effect AVR locus in this pathogen. SNP-based linkage mapping confirmed a single AVR locus within a 14kb map interval containing two genes encoding putative effectors. The Hpa-Cala2 allele of one gene, designated H. arabidopsidis cryptic1 (HAC1), encodes a protein with a signal peptide and an RxLR/dEER motif, and triggers a defence response in RMX-A02. The second gene is heterozygous in Hpa-Cala2. One allele, designated Suppressor of HAC1Cala2 (S-HAC1Cala2) encodes a protein with a signal peptide and a dKEE motif with no RxLR motif; the other allele (s-hac1 Cala2) encodes a protein with a signal peptide, a dEEE motif and is divergent in sequence from the S-HAC1Cala2 allele. In selfed progeny from Hpa-Cala2, dominant S-HAC1Cala2 allele carrying progeny correlates with virulence in RMX-A02, whereas homozygous recessive s-hac1Cala2 carrying progeny were avirulent. Genetic investigations suggested other heterozygous suppressor loci might exist in the Hpa-Cala2 genome.